Influence of impurities (nitrogen and methane) on the CO2 storage capacity as sediment-hosted gas hydrates – Application in the area of the Celtic Sea and the Bay of Biscay. (April 2015) - Burnol, A.; Thinon, I.; Ruffine, L.; Herri, J.-M.
Graphical abstract: Highlights: Investigation of a deep offshore CO2 storage in the Celtic Sea and the Bay of Biscay area. Influence of N2 and CH4 on liquid density and on gas hydrate equilibrium in the high pressure range. First estimates of the CO2 storage capacity in the French EEZ and comparison with the Paris Basin capacity. Abstract: Deep saline aquifers are the most important potential storage reservoirs for CO2 under supercritical conditions. Another option is the trapping of CO2 in deep-sea sediments at low temperature, either in liquid state or as gas hydrates. The Negative Buoyancy Zone (NBZ) and the Gas Hydrate Stability Zone (GHSZ) are used to calculate the theoretical storage volume. It depends essentially on the geothermal gradient and on the quality of the injected CO2 . A sensitivity analysis shows that the storage volume in the Celtic Sea and the Bay of Biscay area is one order of magnitude lower if the injected fluid contains impurities like nitrogen or methane. Overall, the storage capacity in the French Exclusive Economic Zone (EEZ) exceeds 100 years of storage of the current French CO2 emissions from large point sources. The conservative estimate of the EEZ storage capacity is found to be higher than in the deep saline aquifers of the Paris Basin. Moreover, the CO2 storage capacity in this area is doubled when considering the zone beyond 200 miles from the shores. The implications of these results are potentially important for the long-term deployment strategy for CO2 storage in France and in Western Europe.